Evaluación del potencial de un cultivo mixto de microalgas para la depuración de gases de combustión de Diesel (2022)
The use of biotechnologies for the production of value-added products has been gaining strength in recent years, due to the environmental problems that grow day by day, such as the case of the generation of combustion gases, which being the main cause of climate change, trigger the search, development and evolution of technologies that allow the reduction and/or elimination of this type of pollutants; within this search, the development of bioremediation processes and the generation of value-added products through the production of microalgal biomass is highlighted. Considering that the diesel combustion process is one of the major contributors in the generation of greenhouse effect gases, a research project is being developed with the objective of purifying the exhaust gases generated by the Euro III and Euro IV engines in the current fleet of Transmilenio's biarticulated vehicles. The project consists of implementing a system on the vehicle (with a special coupling to the exhaust pipe), consisting mainly of a tubular photobioreactor, inoculated with a mixed culture of microalgae and a gas exchange system by bubbling; this equipment is continuously fed by a cold stream of emitted gases (cooled by a shell-tube heat exchanger), in order to purify these combustion gases and produce biomass.